The Effect of Thyrotropin-Releasing Hormone and Antithyroid Drugs on Fetal Thyroid Function - Nikolaos Vrachnis; Orestis Tsonis; Dionisios Vrachnis; Nikolaos Antonakopoulos; George Paltoglou; Stavroula Barbounaki; George Mastorakos; Minas Paschopoulos; Zoi Iliodromiti (MDPI AG, 2021)
A euthyroid pregnant woman will normally have a fetus that displays normal fetal development. However, studies have long demonstrated the role of T3 (Triiodothyronine), T4 (Thyroxine), and TSH (Thyroid Stimulating Hormone) and their degree of penetrability into the fetal circulation. Maternal thyrotropin-releasing hormone (TRH) crosses the placental site and, from mid-gestation onward, is able to promote fetal TSH secretion. Its origin is not only hypothalamic, as was believed until recently. The maternal pancreas, and other extraneural and extrahypothalamic organs, can produce TRH variants, which are transported through the placenta affecting, to a degree, fetal thyroid function. Antithyroid drugs (ATDs) also cross the placenta and, because of their therapeutic actions, can affect fetal thyroid development, leading in some cases to adverse outcomes. Furthermore, there are a number of TRH analogues that share the same properties as the endogenous hormone. Thus, in this narrative review, we highlight the interaction of all the above with fetal growth in uncomplicated pregnancies.